2015
DOI: 10.1007/s11666-015-0372-6
|View full text |Cite
|
Sign up to set email alerts
|

Cold-Sprayed Cu-MoS2 and Its Fretting Wear Behavior

Abstract: Cu and Cu-MoS2 coatings were fabricated by cold spray and the fretting wear performance of the two coatings was compared. A mixture (95 wt.% Cu + 5 wt.% MoS2) was used as feedstock for the composite coating. Coatings were sprayed with identical gas flow conditions on the substrates preheated to approximately 170C. The morphology of coating top surface and polished cross sections was analyzed by scanning electron microscopy (SEM) and light optical microscopy (LOM). The influence of MoS2 on Cu deposition was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 24 publications
4
6
0
Order By: Relevance
“…2a and b, respectively. The dark contrast along the particle boundaries is MoS2, as shown in our previous work [16,17]. In Fig.…”
Section: Cold-sprayed Coatingssupporting
confidence: 77%
See 2 more Smart Citations
“…2a and b, respectively. The dark contrast along the particle boundaries is MoS2, as shown in our previous work [16,17]. In Fig.…”
Section: Cold-sprayed Coatingssupporting
confidence: 77%
“…100 cycles in both composite coatings (see Fig. [14][15][16][17]. This material flow pattern was believed to be similar to that occurred in fluid flow [42].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Surface strengthening refers to the process of changing the structure of the material surface by applying external force or heat treatment, so as to improve the surface strength, hardness, fatigue resistance, wear resistance, surface integrity. Some common surface strengthening processes in engineering mainly include wet shot-peening [6][7], laser shock [8][9], surface coating [10][11], composite surface strengthening treatment [12][13], etc. A large number of studies have shown that surface strengthening improves the fatigue resistance of materials mainly due to the introduction of residual compressive stress.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study on SLMMC coatings of Cu-MoS2 under gross slip regime demonstrated that presence of MoS2 facilitated fast development of wear debris bed that separated two first bodies and hence protected them from further wear at a low normal load (i.e. 100 N), while at 150 N normal load, a sharp raise in wear volume took place due to poor bonding between Cu and MoS2 [10]. This transition from mild wear to severe wear regimes with increasing normal load was commonly observed in SLMMCs [11].…”
Section: Introductionmentioning
confidence: 99%